Sistem Pakar Berbasis Whatsapp Bot Dengan Metode Forward Chaining Untuk Diagnosis Dini Gangguan Mental Pada Perkembangan Anak - Rayhan Fadhilah; Muhammad Fahri Revansa; Giffari Ahmad Fakhriza; Entin Sutinah; Aryo Tunjung Kusumo (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2025)
Mental disorders in children can hinder their development if not detected early. Limited public awareness and a shortage of professionals often lead to undiagnosed cases. This study developed an expert system based on a WhatsApp Bot using the Forward Chaining method to support early diagnosis of children's mental disorders. Built with Node.js and MySQL, the system can identify seven types of disorders: ADHD, anxiety, depression, autism, OCD, eating disorders, and PTSD. Black box testing showed the system functions well and provides accurate results. It is expected to assist parents and educators in early detection and awareness of mental health issues in children.